Kekerasan Aparat Terhadap Demonstran Dalam Revisi UU TNI: Tinjauan Pidana dan HAM - Pakpahan, Agustinus; Yusuf, Hudi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Freedom of association, assembly, and expression is one of the important rights that both national and international legal instruments have guaranteed. This freedom has certain limitations so that it does not conflict with the rights of others and does not interfere with national security. In terms of securing this act of freedom, law enforcement officers are obliged to respect standard human rights principles that should not be violated, including the use of violence against demonstrators. However, in practice, there are still many cases of repressive actions by law enforcement officers against demonstrators which have become the focus of many parties. The rights of victims of human rights violations by law enforcement officers are often forgotten and unresolved. The violence committed by the authorities against the demonstrators in the Revised TNI Law seems to have made democracy disappear, so what is the purpose of the rule of law in Indonesia? The actions taken by law enforcement officers in this case the Police and TNI (Indonesian National Army) are a serious violation of Human Rights. Citizens who are expressing their voting rights should be protected, not the other way around.